Komparasi Penguasaan Konsep Siswa SMA dan Mahasiswa Pendidikan Fisika Pada Materi Vektor - Yoga Prawendra; Gepi Sartianis; Sentot Kusairi (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
This study aims to determine the difference in conceptual understanding of high school students and physics education students on vector material. This research is a quantitative research with a descriptive approach. The population of this study includes high school students and physics education students have studied vector material physics in East Java. Sampling was done by random sampling for high school students and physics education students in East Java. The instrument used to obtain the data is a conceptual understanding test in the form of 10 multiple choice questions. The results showed that the percentage level of conceptual understanding in high school students was 24% and physics education students 35%. So that students are included in the low category or do not understand while students are included in the medium category or understand. Thus it can be concluded that there are differences in conceptual understanding between high school students and physics education students. This study recommends that further research be conducted to determine the appropriate learning model in improving the understanding of concepts for high school students and physics education students.